1979
DOI: 10.1128/aac.15.6.775
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Experimental Herpes Simplex Encephalitis with Aciclovir in Mice

Abstract: This report is concerned with the capacities of aciclovir to protect mice challenged intracerebrally with multiple lethal doses of type 1 herpes simplex virus and to control multiplication of this virus in the brain. With treatment initiated 12 h after inoculation and continued for 4 consecutive days, aciclovir administered subcutaneously in daily doses ranging from 40 to 100 mg/kg led to 21-day survival rates of from 33 to 73% and reduced virus titers by 1 to 1,h x 4 logs on postchallenge day 8. The therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The significant weight loss noted with ACV or ara-A at a dose of 400 mg/kg was consistent with that reported previously (18,21). Weight loss was also noted when FIAC or FMAU was given twice a day for 4 days at doses equal to or greater than 800 and 400 mg/kg per day, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…The significant weight loss noted with ACV or ara-A at a dose of 400 mg/kg was consistent with that reported previously (18,21). Weight loss was also noted when FIAC or FMAU was given twice a day for 4 days at doses equal to or greater than 800 and 400 mg/kg per day, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Except for Epstein-Barr virus, these viruses share the property of expressing a virus-specified thymidine kinase that converts ACV to acycloguanosine monophosphate, which is further phosphorylated by host cell guanosine monophosphate kinase and other kinases (13) to its active form, acycloguanosine triphosphate, which inhibits the viral deoxyribonucleic acid (DNA) polymerase (7,9,10). Studies of HSV infections in mice treated with ACV have shown reduction in morbidity, mortality, and organ virus titers (8,12,16). We have found the in vitro susceptibility of mouse cytomegalovirus (MCMV) to ACV to be comparable to that reported for HSV types 1 and 2 and varicellazoster virus (Burns et al, unpublished data).…”
supporting
confidence: 59%
“…Hairless mice inoculated with HSV into the skin also experienced less severe local inflammation and reduced mortality with ACV treatment (12). In a mouse model of HSV encephalitis, ACV decreased mortality, brain virus titers, and weight loss (16). Also, if ACV treatments were started early enough and continued sufficiently long, the establishment of latent infection of dorsal root ganglia after skin inoculation was reduced.…”
mentioning
confidence: 90%
“…HSV infections in mice. These compounds are 9-1-Darabinofuranosyladenine (5,15,22,26,27), its 5'-monophosphate (19), 1-P-D-arabinofuranosylthymine (19), and 9-(2-hydroxyethoxymethyl)guanine (acycloguanosine, acyclovir) (4,22,24). Akin to BVDU, all three arabinofuranosyl derivatives, as well as acyclovir, provide significant protection against HSV-1 encephalitis when administered s.c. or i.p.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies cannot be considered as truly representative for a systemic VOL. 22,1982 on April 29, 2019 by guest http://aac.asm.org/ Downloaded from therapy of herpetic encephalitis since, on the one hand, 5-trifluoromethyl-2'-deoxyuridine was injected i.c. (simultaneously with the virus inoculum) (6) and, on the other hand, the efficacy of 5-ethyl-2'-deoxyuridine was evaluated in mice which had been infected s.c. (7).…”
Section: Resultsmentioning
confidence: 99%